Social influence processes on adolescents' food likes and consumption: the role of parental authoritativeness and individual self‐monitoring. Issue 2 (30th July 2015) - Guidetti, Margherita; Cavazza, Nicoletta; Conner, Mark
Abstract: This cross‐sectional study investigated how parents and friends influence adolescents' food likes and consumption. 709 adolescent‐parent and 638 adolescent‐friend dyads completed a questionnaire, allowing us to compare target‐parent and target‐friend resemblances both on food likes and consumption, while distinguishing between cultural influence and dyadic unique influence. In addition, we identified two psychosocial predictors of resemblance, namely parenting style and adolescents' self‐monitoring. As expected, results indicated that authoritative parenting style increased target‐parent resemblance in food likes (directly) and consumption (indirectly), and self‐monitoring orientation increased target‐friend resemblance in food likes (directly) and consumption (indirectly). We also showed that target‐friend resemblance was more culture‐based than target‐parent resemblance, suggesting that parental influence is more specific to the dyadic relation than is peer influence.